Metal-free nitrile diboration through activation by an electron-rich diborane - Frick, Markus; Kaifer, Elisabeth; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2017)
Diboration of unsaturated organic compounds is an extremely useful reaction in synthetic chemistry. Herein, we report the first diboration of a nitrile by an electron-rich diborane, mediated by an electrophilic borane. The reaction is metal-free, and all of the reagents are readily available.